INTERACTIVE MATERIALS FOR TEACHING SPOKEN NARRATIVE TEXTS BASED ON INDONESIAN FOLKTALES - Farida, Lulu April; Sofwan, Ahmad (Universitas Negeri Semarang, 2012)
Penelitian ini bertujuan mengembangkan bahan ajar interaktif dengan mendaptasi cerita rakyat Indonesia, dan mengkaji penggunaannya dalam pengajaran teks naratif lisan bagi siswa SMP. Penelitian ini adalah penelitian pengembangan dengan memodifikasi model Gall, Gall & Borg dan Thiagarajan, Semmel, & Melvyn. Hasil penelitian menunjukkan bahwa guru dan siswa membutuhkan bahan ajar interaktif untuk menjadikan pembelajaran lebih efektif. Sesudah dievaluasi oleh pakar, prototipe bahan ajar direvisi dan diujikan di dua SMP. Hasil analisis menunjukkan bahwa produk itu dapat digunakan dengan baik di kelas dan siswa mencapai kompetensi yang diharapkan pada ketrampilan mendengarkan dan membaca. Siswa dan guru berpendapat bahwa bahan ajar itu efektif dan berguna bagi mereka untuk belajar Bahasa Inggris. Disimpulkan bahwa bahan ajar interaktif yang dikembangkan dari adaptasi cerita rakyat Indonesia berbentuk Widuri Game terbukti dapat diterapkan dan efektif untuk meningkatkan ketrampilan lisan siswa.Ã‚Â This study aims at developing interactive teaching materials by adapting Indonesian folktales, and examining their implementation for teaching spoken narrative texts to junior high school students. A research and development (R&D) method with six stages was used in this study. The results show that the teachers and students require interactive materials that could make the teaching learning activities more effective. After being evaluated by experts, the prototype was revised and field-tested in two junior high schools. The results showed that the product was successfully implemented in the classroom in that the students could achieve the passing grade for both listening and speaking tests. The students also perceived that the product was effective and useful for them to learn English. The teachers perceived that the product was good and excellent to be used in the classroom. Therefore, it could be concluded that Widuri Game, the interactive materials adapted from Indonesian folktales was practical and effective to improve the studentsÃ¢â‚¬â„¢ oral competence skill.